Mendelian randomisation for nutritional psychiatry. (February 2020) - Carnegie, Rebecca; Zheng, Jie; Sallis, Hannah M; Jones, Hannah J; Wade, Kaitlin H; Evans, Jonathan; Zammit, Stan; Munafò, Marcus R; Martin, Richard M
Summary: Nutritional psychiatry is a growing area of research, with several nutritional factors implicated in the cause of psychiatric ill-health. However, nutritional research is highly complex, with multiple potential factors involved, highly confounded exposures and small effect sizes for individual nutrients. This Personal View considers whether Mendelian randomisation provides a solution to these difficulties, by investigating causality in a low-risk and low-cost way. We reviewed studies using Mendelian randomisation in nutritional psychiatry, along with the potential opportunities and challenges of using this approach for investigating the causal effects of nutritional exposures. Several studies have identified nutritional exposures that are potentially causal by using Mendelian randomisation in psychiatry, offering opportunities for further mechanistic research, intervention development, and replication. The use of Mendelian randomisation as a foundation for intervention development facilitates the best use of resources in an emerging discipline in which opportunities are rich, but resources are often poor.